PENERAPAN MODEL PERKULIAHAN BERDASARKAN PROBLEM-BASED INSTRUCTION DALAM MATA KULIAH GEOLOGI (Kasus pada Program Studi Pendidikan Geografi FKIP UNISMA) - Hermanto . (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2005)
Learning model by problem-based instruction is an approach of learning method of student toward authentic problem. The research is to know: (!) outcome of learning of student after studying with learning model by problem-based instruction and compared with outcome of student learning by conventional method. And (2) The effectiveness of learning model by problem-based method in action to transfer the material of geology. The result of research shows that outcome of learning of student with learning method by problem-based method is betther than student with conventional method.